Use of Underground Mining Activities in Earthquake Search and Rescue Works - Süleyman Sırrı Sargın; Cem Şensöğüt (International Journal of Economic and Environment Geology)
Although the mining sector has the task of providing raw materials directly or indirectly to industrial establishments, it unfortunately contains great dangers and risks for its employees in terms of occupational health and safety. Especially in mining enterprises operating underground, roof collapse, sudden gas discharge, flooding, gas explosions etc. negativities that occur during production cause great material and moral destruction. In such big problems, well-trained rescue teams of mines play an important role in saving the lives of many miners.Earthquake disasters affecting 11 provinces in Turkeycaused great destruction, many people died in building debris and collapses, and buildings and industrial facilities were severely damagedon Feb. 6 2023. In the search and rescue works that started after the earthquake, the outstanding efforts of the underground mine workersin the field and the methods they used in these studies attracted the attention of the public.In this study, evaluations were made by giving some underground rescue methods used in search and rescue activities in the Adıyaman earthquake regionwhich is one of 11 provinces affectedby the disaster in Turkey.